2023
DOI: 10.3389/fsurg.2022.927637
|View full text |Cite
|
Sign up to set email alerts
|

An ingested metallic wire migrating from stomach to pancreas treated by laparoscopic surgery: A case report

Abstract: IntroductionForeign bodies inside the pancreas are rare and usually occur after the ingestion of sharp objects such as a fish bone, a sewing needle, or a toothpick. Furthermore, an ingested metallic wire migrating from stomach to pancreas is very rare.Case PresentationWe report a 36-year-old woman who was admitted to our hospital with “3-day history of dull progressive epigastric pain.” Computed tomography of the abdomen revealed a linear, high-density body between the stomach wall and the pancreas. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…4 Hao et al in 2022 reported the case of 36/F presenting with dull epigastric pain, whose CT demonstrated a similar liner high density foreign body extending from the posterior gastric wall and embedded in the pancreas; a 3 cm metallic wire was removed on surgery and was assumed to have been ingested from remnants of a metallic brush used to clean pots and pans. 25 There was, however, no abscess formation/ inflammation or pancreatitis in this patient. Sulieman et al in 2022 reported a case of an accidentally ingested metallic grill brush wire masquerading as peripancreatic and paraduodenal inflammation on CT.…”
Section: Discussionmentioning
confidence: 61%
“…4 Hao et al in 2022 reported the case of 36/F presenting with dull epigastric pain, whose CT demonstrated a similar liner high density foreign body extending from the posterior gastric wall and embedded in the pancreas; a 3 cm metallic wire was removed on surgery and was assumed to have been ingested from remnants of a metallic brush used to clean pots and pans. 25 There was, however, no abscess formation/ inflammation or pancreatitis in this patient. Sulieman et al in 2022 reported a case of an accidentally ingested metallic grill brush wire masquerading as peripancreatic and paraduodenal inflammation on CT.…”
Section: Discussionmentioning
confidence: 61%
“…Another hypothesis is that the glass bodies might have taken a more distal route, such as transgastric or transenteric, from which they would have spread further within the body. It is estimated that around 1% of swallowed foreign bodies penetrate the gastric and duodenal wall, traveling within the abdominal cavity and potentially reaching the liver, pancreas, spleen or even further into the thoracic cavity 28,33 . Our literature review revealed 41 cases of intrapancreatic foreign bodies (Table 3), including 14 suture needles, 23–31 4 metal wires, 32–35 19 fish bones, 7,36–47,49–54 2 other pointed bones 55,56, and 2 toothpicks 57,58 .…”
Section: Discussionmentioning
confidence: 96%
“…There are documented cases where a substantial amount of glass shards were deliberately ingested but successfully passed through the digestive tract without perforation 90,91 . Although foreign bodies sometimes pass through the intestine within a week without complications, larger objects, and especially pointed bodies, do increase the risk of injury 4,33,92 . It is estimated that approximately 12% of esophageal perforations are attributed to the ingestion of foreign bodies 93 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations